THE AWARENESS ANALYSIS OF DIGITAL MARKETING IN RETAIL INDUSTRY- A STUDY WITH REFERENCE TO ANDHRA PRADESH - T. Srilakshmi; R. Sai Sandeep Kumar; V. Madhava Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The current study carries numerous aspects like recent trends, attitudes of buyers and how they participate in the digital marketing in retail sector. The researcher identifying the satisfaction of the consumers, perceptions and their problems towards the digital marketing in retail stores. The researcher utilizes both the primary and secondary data for the research. The researcher uses books, magazines, newspapers, journals etc. as the second-hand data. And survey method is used as primary data for this research. Convenience sampling technique is used. The researcher analyzes the current study with the help of the percentages and mean